Accountability answers company insurance life based investing against the risk of failure to pay for policyholders - Santri, Selvi Harvia; Yaswirman, Yaswirman; Warman, Kurnia; Fauzi, Wetria (Linguistics and Culture Review, 2022)
The problem of this research is how to regulate investment-based life insurance in Indonesia and the liability of investment-based life insurance companies against the risk of default by policyholders. This study uses a research method that has an empirical juridical type. The study results explain that the regulation of investment-based life insurance in Indonesia is regulated in Law Number 40 of 2014 concerning Business Per Insurance, OJK Regulation Number 23/POJK.05/2015 concerning Insurance Products and Marketing and Decree of the Chairman of BPPM and Financial Institutions Number KEP-104/ BL/2006 concerning Investment-based life insurance products. PP Number 87 of 2019 concerning insurance companies in the form of joint ventures, RI's Financial Decree Number 422/KMK.06/2003 and Director General of Financial Institutions Decree Number 2475/LK concerning investment insurance products and forms of liability of default insurance companies must fulfill the contents of the agreement insurance that gives rise to the rights and obligations of the insured reciprocally. However, Law Number 40 of 2014 concerning Insurance Business does not fully regulate violations in the insurance business and does not regulate how the insurance company is responsible for the company's inability to fulfill insurance claims.